Circular RNA circASS1 is downregulated in breast cancer cells MDA-MB-231 and suppressed invasion and migration. (18th January 2019) - Hou, Jun-chen; Xu, Zhi; Zhong, Shan-liang; Zhang, He-da; Jiang, Lin-hong; Chen, Xiu; Zhu, Ling-ping; Li, Jian; Zhou, Si-ying; Yang, Su-jin; He, Yun-jie; Wang, Dan-dan; et al.
Aim: The study aimed to investigate the role of circular RNA circASS1 in breast cancer cells.Materials & methods: Circular RNAs microarray expression profile were analyzed in MCF-7, MDA-MB-231, and qRT-PCR and western blotting were used to quantify expression of circASS1 and its parental gene ASS1 . Wound healing, migration and invasion assay were performed. Luciferase assay system was used to detect harbored miRNA.Results: CircASS1 in MDA-MB-231 is downregulated comparing to MCF-7, and overexpression of circASS1 could suppress invasion and migration. While silence, it could promote invasion and migration. MiR-4443 functioning as a tumor promoter gene could be captured by circASS1. ASS1 is upregulated in loss-of-function experiments, while downregulated in gain-of-function experiments.Conclusion: CircASS1 suppresses invasion and migration capacity of breast cancer cells and harbored miR-4443.